2020
DOI: 10.1111/1365-2656.13324
|View full text |Cite
|
Sign up to set email alerts
|

Life‐history genomic regions explain differences in Atlantic salmon marine diet specialization

Abstract: Animals employ various foraging strategies along their ontogeny to acquire energy, and with varying degree of efficiencies, to support growth, maturation and subsequent reproduction events. Individuals that can efficiently acquire energy early are more likely to mature at an earlier age, as a result of faster energy gain which can fuel maturation and reproduction. 2. We aimed to test the hypothesis that heritable resource acquisition variation that co-varies with efficiency along the ontogeny would influence m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 108 publications
(173 reference statements)
1
36
5
Order By: Relevance
“…In the last few decades, many Atlantic salmon populations have been maturing, on average, at younger ages 46 , which is associated with a change in vgll3 allele frequency in some cases 47 . Recently, a link was found between the decrease in salmon age-at-maturity and a change in prey species composition 48 (see also 49 for diet composition in relation to six6). These observations further highlight that genotype dependent differences in SMR or aerobic performance, which can contribute to foraging success or food assimilation (e.g., 22,50,51 ), may be related to contemporary life-history evolution in Atlantic salmon.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, many Atlantic salmon populations have been maturing, on average, at younger ages 46 , which is associated with a change in vgll3 allele frequency in some cases 47 . Recently, a link was found between the decrease in salmon age-at-maturity and a change in prey species composition 48 (see also 49 for diet composition in relation to six6). These observations further highlight that genotype dependent differences in SMR or aerobic performance, which can contribute to foraging success or food assimilation (e.g., 22,50,51 ), may be related to contemporary life-history evolution in Atlantic salmon.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is unclear how genetic factors interact with diet to influence maturation. A recent study by Aykanat et al (2020) quantified the stomach contents of wild adult Atlantic salmon and demonstrated that the six6 genomic region is linked to gut fullness as well as prey composition, while vgll3 was marginally linked to prey composition. These results suggest that Atlantic salmon is not only a diet specialist governed by genetic variation in six6, but that the genetic basis of diet variation is linked to maturation.…”
Section: Marine Phasementioning
confidence: 99%
“…5). Repeat-spawning is also linked to the vgll3 locus (Aykanat et al 2020) and early maturing individuals may recover additional reproductive success if they survive to reproduce again. A survey of 57 populations has shown that vgll3 alleles are maintained at intermediate frequencies in many populations (Barson et al 2015), which may be indicative of balancing selection, predicted under intra-locus sexual conflict (Connallon and Clark 2014).…”
Section: Marine Phasementioning
confidence: 99%
“…Genotypes at this locus were entirely consistent with the previously known reproductive ecotypes including shore/deep-spawning kokanee (East Barrière Lake: GG genotype in 31/31 samples; Anderson Lake: GG genotype in 21/23 samples; Seton Lake: GG genotype in 22/22 samples), streamspawning kokanee (Nicola Lake: GG genotype in 0/25 samples); and stream-spawning sockeye salmon (Portage Creek: GG genotype in 0/23 samples; Scotch Creek: GG genotype in 0/25 samples). In Atlantic salmon, LRRC9 is located 142 kb away from the six6 gene that exhibits signatures of divergent selection with respect to spawning ecotypes and has been associated with age at maturity (Barson et al, 2015) and marine diet specialization (Aykanat et al, 2020).…”
Section: Outlier Loci and Ecotype Identificationmentioning
confidence: 99%